Lectotypification and a new synonym in Palicourea (Rubiaceae) - Carla Y’ Gubáu Manão; Roberto Lourenço Esteves; Sebastião José da Silva Neto (Anales del Jardín Botánico de Madrid, 2016)
Here we designate specimen no. 10424 from the Museu Nacional (R) as the lectotype of Palicourea rudgeoides (Müll. Arg.) Standl. [Psychotria rudgeoides Müll. Arg., basion.], and assign a new synonym for Palicourea fulgens (Müll. Arg.) Standl., Psychotria exannulata Müll. Arg., based on specimen no. 607125 from the Field Museum of Natural History (F).